Effect of sodium hexametaphosphate and quercetin, associated or not with fluoride, on dentin erosion in vitro - Capalbo, Letícia Cabrera [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Dal-Fabbro, Renan; Inácio, Kelly Karina; de Oliveira, Rodrigo Cardoso; Pessan, Juliano Pelim [UNESP] (Elsevier, 2022)
Objective: to investigate the ability of solutions containing sodium hexametaphosphate, fluoride and quercetin, alone or in association, to prevent dentin erosion and to inhibit matrix metalloproteinases -2 and -9 activity using in vitro protocols. Design: Root dentin blocks (n = 96) were prepared and divided into 8 experimental groups (n = 12/group), according to the solutions to be tested: Placebo; 0.24% sodium fluoride (F); 1.0% sodium hexametaphosphate (HMP); 0.03% quercetin (QC); F+HMP; F+QC; HMP+QC; and F+HMP+QC. Erosive challenges were performed 4×/day for 5 days. Specimens were treated with the respective solutions for one minute, twice a day. Next, dentin loss (profilometry) and integrated hardness area in depth (KHN × µm) were determined. The antiproteolytic potential was assessed by gelatin zymography. Dentin erosion results (log10-transformed) were submitted to one-way ANOVA, followed by Tukey's test. Integrated hardness area in depth data (raw) were submitted to two-way, repeated-measures ANOVA, followed by Holm-Sidak's test (p<0.05). Results: Dentin erosion was significantly lower for F+HMP+QC than for all other treatments. At the shallowest depths (5–30 µm), blocks treated with F+HMP+QC had the highest integrated hardness area in depth values. All treatments completely inhibited matrix metalloproteinases-2 activity, except for the group QC (77% inhibition). For matrix metalloproteinases-9, all HMP-containing solutions or F+QC promoted total antiproteolytic activity. Conclusion: The association of fluoride, sodium hexametaphosphate, and quercetin must be considered a valuable strategy for novel product formulation for home and professional use, considering its superior protective effects against dentin erosion and its antiproteolytic potential.
Keywords: Dentin; Matrix metalloproteinase inhibitors; Polyphosphates; Quercetin; Tooth erosion